Cell-by-cell scanning of whole mitochondrial genomes in aged human heart reveals a significant fraction of myocytes with clonally expanded deletions - Konstantin Khrapko; Natalya D. Bodyak; William G. Thilly; Nathalie J. van Orsouw; Xianfeng Zhang; Hilary A. Coller; Thomas T. Perls; Melissa P. Upton; Jan Vijg; Jeanne Y. Wei (1999)
Quantitative information on the cell-to-cell distribution of all possible mitochondrial DNA (mtDNA) mutations in young and aged tissues is needed to assess the relevance of these mutations to the aging process. In the present study, we used PCR amplification of full-length mitochondrial genomes from single cells to scan human cardiomyocytes for all possible large deletions in mtDNA. Analysis of more than 350 individual cells that were derived from three middle-aged and four centenarian donors demonstrates that while most of the cells contain no deletions, in certain cardiomyocytes a significant portion of the mtDNA molecules carried one particular deletion. Different affected cells contained different deletions. Although similar numbers of cells were screened for each donor, these deletion-rich cells were found only in the hearts of old donors, where they occurred at a frequency of up to one in seven cells. These initial observations demonstrate the efficiency of the method and indicate that mitochondrial mutations have the potential to play an important role in human myocardial aging.